Is speech function lateralised in the basal ganglia? Evidence from de novo Parkinson's disease - Rusz, Jan; Dusek, Petr; Tykalova, Tereza; Novotny, Michal; Illner, Vojtech; Simek, Michal; Kouba, Tomas; Kryze, Petr; Zogala, David; Ruzicka, Evzen; Sousa, Mário; Jorge, Adriana; et al. (Journal of neurology, neurosurgery and psychiatry, 2025)
BACKGROUND: Research on the possible influence of lateralised basal ganglia dysfunction on speech in Parkinson's disease is scarce. This study aimed to compare speech in de-novo, drug-naive patients with Parkinson's disease (PD) with asymmetric nigral dopaminergic dysfunction, predominantly in either the right or left hemisphere. METHODS: Acoustic analyses of reading passages were performed. Asymmetry of nigral dysfunction was defined using dopamine transporter-single-photon emission CT (DAT-SPECT). RESULTS: From a total of 135 de novo patients with PD assessed, 47 patients had a lower right and 36 lower left DAT availability in putamen based on DAT-SPECT. Patients with PD with lower left DAT availability had higher dysarthria severity via composite dysarthria index compared with patients with lower right DAT availability (p=0.01). CONCLUSION: Our data support the crucial role of DAT availability in the left putamen in speech. This finding might provide important clues for managing speech following deep brain stimulation.
Keywords: řeč; Dopamine Plasma Membrane Transport Proteins; Putamen; Male; Speech; Tomography, Emission-Computed, Single-Photon; bazální ganglia; jednofotonová emisní výpočetní tomografie; Aged; mužské pohlaví; senioři; putamen; lidé; ženské pohlaví; Basal Ganglia; Humans; proteiny přenášející dopamin přes plazmatickou membránu; Functional Laterality; Dysarthria; Female; dysartrie; Parkinsonova nemoc; Parkinson Disease; lidé středního věku; funkční lateralita; Middle Aged